Exploring Factors Affecting the Decision to Buy “Miniso” Bag in Shopee Aplication: Case Study among Students of STES Islamic Village - muizzudin Muizzudin; Julia Safitri (ISLAMINOMICS: JOURNAL OF ISLAMIC ECONOMICS, BUSINESS AND FINANCE, 2022)
The objective of this research is to see the impact of the price, product quality, and brand image on the decision to buy “Minoso” bag in Shopee among students of STES Islamic Village. The research uses three independent variables: price (X1), quality product (X2), and brand image (X3) and one dependent variable: decision to buy (Y). The population are the students of four said institutions.  With the purposive samping, there are 90 respondents. This research applies the descriptive quantitative method with multiple linear regression to test the impact of three independent variables observed on the only one dependent variable observed. To support the data analysis, the research makes the best use of SPSS 26 for windows. The research results show that partially X1 (price) and X2 (quality product) do not influence Y (the decision to buy) significantly while the brand image influences Y significantly.